2019
DOI: 10.3892/mco.2019.1830
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between stereotactic radiosurgery and whole‑brain radiotherapy for 10‑20 brain metastases from non‑small cell lung cancer

Abstract: The efficacy and safety of stereotactic radiosurgery (SRS) in comparison with whole brain radiotherapy (WBRT) for brain metastases (BMs) remains unclear. The present study retrospectively reviewed 44 patients who received SRS or WBRT as an initial treatment for 10-20 BMs from non-small cell lung cancer between 2009 and 2016. Of the patients, 24 (54.5%) were treated with SRS and 20 (45.5%) were treated with WBRT. Overall survival (OS), time to intracranial progression (TTIP), neurological survival (NS), and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…A larger measurement delay was also observed with higher motion speed especially for OSMS due to its lower frame rate. Stereotactic radiosurgery (SRS) has become a popular tool to treat intracranial brain metastases due to convenience for the patients, durable local control and the possibility of reduced cognitive impairment versus whole brain radiotherapy [18][19][20]. Thomas et al reported that mean delivery time was 1.7 min per target for linacbased SRS using flattening-free beam (FFF) and an average 31.6 min delivery per target for GK-SRS [21].…”
Section: Discussionmentioning
confidence: 99%
“…A larger measurement delay was also observed with higher motion speed especially for OSMS due to its lower frame rate. Stereotactic radiosurgery (SRS) has become a popular tool to treat intracranial brain metastases due to convenience for the patients, durable local control and the possibility of reduced cognitive impairment versus whole brain radiotherapy [18][19][20]. Thomas et al reported that mean delivery time was 1.7 min per target for linacbased SRS using flattening-free beam (FFF) and an average 31.6 min delivery per target for GK-SRS [21].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is an effective treatment for brain metastasis, especially for multiple brain metastases patients. Currently, radiotherapy for multiple brain metastases is a WRBTbased radiation mode (4)(5)(6). Studies have reported that stereotactic radiotherapy or hypofractionated radiation therapy has better efficacy and less adverse reactions, and tends to be chosen over WBRT (7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…A larger measurement delay was also observed with higher motion speed especially for OSMS due to its lower frame rate. Stereotactic radiosurgery (SRS) has become a popular tool to treat intracranial brain metastases due to convenience for the patients, durable local control and the possibility of reduced cognitive impairment versus whole brain radiotherapy [15][16][17]. Thomas et.…”
Section: Discussionmentioning
confidence: 99%